1985
DOI: 10.1063/1.335698
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum surface flashover: A high-pressure phenomenon

Abstract: Articles you may be interested inEnhanced surface flashover strength in vacuum of polymethylmethacrylate by surface modification using atmospheric-pressure dielectric barrier discharge A simple highpressure reaction chamber connected to an ultrahigh vacuum system for surface studies J. Vac. Sci. Technol. A 5, 234 (1987); 10.1116/1.574110 Surface flashover of conical insulators in vacuum J. Appl. Phys. 56, 1374 (1984); 10.1063/1.334128 Surface flashover of solid dielectric in vacuumDesorbed gases from insulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Surface flashover of insulators in vacuum is generally the limiting factor in the design of high voltage vacuum devices. The most widely-accepted theory of surface flashover holds that --an avalanche of secondary electrons occurs along the insulator surface, desorbing gas through which the breakdown occurs [4][5][6][7]. The HGI overcomes the flashover by inhibiting the breakdown process using closely-spaced, floating conductors, encapsulated in a dielectric.…”
Section: High-gradient Insulatormentioning
confidence: 99%
“…Surface flashover of insulators in vacuum is generally the limiting factor in the design of high voltage vacuum devices. The most widely-accepted theory of surface flashover holds that --an avalanche of secondary electrons occurs along the insulator surface, desorbing gas through which the breakdown occurs [4][5][6][7]. The HGI overcomes the flashover by inhibiting the breakdown process using closely-spaced, floating conductors, encapsulated in a dielectric.…”
Section: High-gradient Insulatormentioning
confidence: 99%
“…In SEEA charging, 6,8,13,34 the surface charge density can be expressed by: where σ is the positive surface charge; E ⊥ is the electric field perpendicular to the sample surface; and ε 0 is the permittivity of free space.…”
Section: Simulation Modelmentioning
confidence: 99%
“…The limited literature search [14][15][16][17][18][19] indicated that surface flashover in vacuum seems to be triggered by charge injection into the dielectric at the triple points at the ends of the insulator. Surface composition and condition also affect flashover.…”
Section: Basis For Scale Model Testingmentioning
confidence: 99%